2011
DOI: 10.5251/abjna.2011.2.6.907.920
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salinity stress on growth parameters, photosynthetic activity and cytological studies of Zea mays, L. plant using hydrogel polymer

Abstract: The effects of incorporating a hydrogel polymer with sand on development of selected maize (Zea mays, L.) grown under saline conditions has been demonstrated. The seeds of maize was germinated in sand/swollen hydrogel polymer mixture (80:20 v/v) with added Hoagland nutrient solution, then transplanted after 7 days from germination into a range of sand/swollen hydrogel polymer (90:10 v/v) in plastic growbags. Saline solutions containing NaCl, CaCl 2 , mgCl 2 (0.0, 2,000, 4,000, 6,000, 8,000 ppm.)were applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 74 publications
(32 reference statements)
3
19
1
Order By: Relevance
“…The higher level of NaCl (200 mM NaCl) caused the reduction of shoot growth in addition to wilting of plants. These results are in accordance with the previous reports where reduction of shoot growth due to salt stress in maize have been reported (Pitann et al 2009/a;Pitann et al 2009/b;Szalai and Janda 2009;El Sayed 2011). Szalai and Janda (2009) reported the decrease in elongation rate as well as the number of elongating cells caused this reduction of shoot growth.…”
Section: Discussionsupporting
confidence: 93%
“…The higher level of NaCl (200 mM NaCl) caused the reduction of shoot growth in addition to wilting of plants. These results are in accordance with the previous reports where reduction of shoot growth due to salt stress in maize have been reported (Pitann et al 2009/a;Pitann et al 2009/b;Szalai and Janda 2009;El Sayed 2011). Szalai and Janda (2009) reported the decrease in elongation rate as well as the number of elongating cells caused this reduction of shoot growth.…”
Section: Discussionsupporting
confidence: 93%
“…A reduction in photosynthetic pigments such as chlorophylls a and b and carotenoids is also associated with a decline in the net photosynthesis rate in maize under salt stress (El Sayed 2011;Qu et al 2012). Cha-um and Kirdmanee (2009) observed a linear reduction in chlorophylls a and b, total chlorophyll, and carotenoid contents in maize with increased salt stress.…”
Section: Light Harvesting and Carbon Fixationmentioning
confidence: 99%
“…As a salt-sensitive crop, shoot growth in maize is strongly inhibited in the first phase of salt stress (Pitann et al 2009a, b;Szalai and Janda 2009;El Sayed 2011;Wakeel et al 2011a). De Costa et al (2007) observed stunted maize growth with dark green leaves without any toxicity symptoms during the first phase of salt stress, owing to impaired extension growth as osmotic adjustment and turgor maintenance were not limiting.…”
Section: Germination and Plant Growthmentioning
confidence: 99%
“…Decline in relative water content (RWC) has been reported in all maize varieties in saline environments (Sairam et al, 2002). El Sayed (2011) reported decline in the photosynthetic pigments in maize (Zea mays L.) crop under NaCl stress conditions. Hydrogen peroxide (H2O2) level is maintained inside the cell by various types of antioxidant enzymes like peroxidase (POD) and catalase (CAT) (Foyer and Noctor, 2003).…”
Section: Discussionmentioning
confidence: 99%